Add-on effects of oral tocopherol supplementation to surgical varicocelectomy on the outcome of assisted reproductive technology: a single-center pilot study report - Takeshima, Teppei; Mihara, Takahiro; Tomita, Makoto; Kuroda, Shinnosuke; Yumura, Yasushi; Ueno, Hiroe; Yamamoto, Mizuki; Murase, Mariko (Frontiers in Reproductive Health, 2024)
This is a provisional file, not the final typeset articleNo significant differences were observed in the pregnancy rate per couple (tocopherol group, 70.9% vs. control group, 64.9%, P = 0.55) and per embryo transfer (50.4% vs. 39.6%, P = 0.22). Regarding the time to event analyzed by adjusted restricted mean survival time, the mean time to pregnancy was significantly shorter in the antioxidant group (14.2 vs. 17.4 months, P = 0.025). No significant difference was observed in the embryo transfer cycle to pregnancy (mean embryo transfer cycles: 2.6 vs. 3.0, P = 0.238).Additional oral tocopherol nicotinate as antioxidant therapy after varicocelectomy was shown to shorten the time to pregnancy. It is recommended that add-on effects be tested in more well-designed randomized controlled trials to examine whether it improves assisted reproductive outcomes.